Rancang Bangun Sistem Terdistribusi pada Toko Roti Valentine Tanjung Jabung Barat - Andrico, Ricky; Hetty Rohayani; Novia, Tri Meli; Amandha, Shandy (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
A bakery is a business operating in the food sector that sells various kinds of bread and cake products and sometimes they sell drinks, food and products related to the cake and bread industry. Data collection for all aspects of previous sales uses memory and by recording it in books or on paper. This journal was written using a distributed system method. Due to the ineffectiveness of existing data collection, to prevent errors in information collection, this system was created to be a solution to this problem. With the aim of increasing effectiveness, this system was created.